Mineralogical and Geochemical Variations in the Regolith of Mokuro-Itagunmodi Area, Ife-Ilesa Schist Belt, Southwestern Nigeria - Ajidahun, Emmanuel Jeminiyi (2015)
The geochemistry of regolith overlying basement rocks in Mokuro-Itagunmodi area along selected road-cut sections and petrography of the rocks were investigated with a view to determining the mineralogy, major and trace element concentrations and their distribution patterns in relation to the bedrock.